"Instigator Korfanty" or "The Master Advertiser"? Wojciech Korfanty as the Polish Plebiscite Commissioner and the Silesian Uprisings Dictator. Overview of the German Liberal Daily Press (Zaranie Śląskie, 2022)
The present study examines the image of Wojciech Korfanty as Polish voting commissioner in Upper Silesia in the reporting of four German liberal daily newspapers (Berliner Tageblatt, Deutsche Allgemeine Zeitung, Frankfurter Zeitung, Kölnische Zeitung) from the Weimar Republic. Initially trying to accompany him with a certain distance and prejudice and to give him actual recognition for his rhetorical skills and skilful propaganda activities, Korfanty quickly became the preferred object of German attacks and the third uprising, the intensity and vehemence of the appropriate criticism reached an unimagined level. It cannot be overlooked that during this time the press constantly tried to counter Korfanty himself and his actions with disavowing reports. He thus rose to become the protagonist of German agitation in Up-per Silesia and remained continuously the centre of attention of German attacks. A look at the German liberal newspapers based on the results obtained shows an extremely one-sided and unreservedly negative image of Wojciech Korfanty as the Polish voting commissioner, who terrorized the (German) population in Upper Silesia with his activities and terrified them. But in the statements he was not only associated with hate speech, murder and agitation. In the course of his activities in the voting area, he was seen with his intentions and demands as the embodiment of the Polish dismemberment efforts, who only wanted to cause suffering and damage to the whole Upper Silesian country.
Keywords: Wojciech Korfanty; Upper Silesia; Upper Silesia plebiscite; liberal press; Silesian Uprisings